PENENTUAN WILAYAH RAWAN PENYAKIT BERBASIS LINGKUNGAN DI JAKARTA TIMUR MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Redaksi Tim Jurnal (PETIR, 2016)
East Jakarta is one of Jakarta areas that are prone to diseases Dengue Hemorrhagic Fever (DHF), Acute Respiratory Infections (ARI) and diarrhea. The Statistics data from Sub Department of Health, East Jakarta show that the level of vulnerability to dengue disease reached 100%, 40% of ARI and diarrhea 10%. Unfortunately, the data figures were less describe the actual situation spatially. This research was conducted to determine areas vulnerable to desease based on spatial environment in East Jakarta using Geographic Information System (GIS). The category of desease which is the object of this research are the dengue disease, respiratory infection and diarrhea. The method used to determine disease susceptibility is scoring and overlay method. Based on the analysis with GIS, there are two levels of vulnerability to the disease namely "Vulnarable" and "Very Vulnerable" with details nine of the ten sub-districts in East Jakarta are in the status of "Vulnerable" and only one region with the status "Very Vulnerable" namely Ciracas District. The results of this analysis is expected to help the society health centers in East Jakarta in monitoring the spread of the disease and the risks so that they can anticipate and providing services as early and effectively as possible .